Dhatu Sarata in Rachana Sharir: An Anatomical Study of Structural Strength of the Human Body - Verma, Piyush Kumar; Phate, Rahul R; Meena, Neeraj Kumar; Menka (International Research Journal of Ayurveda & Yoga, 2026)
Ayurveda explains the structural strength of the human body through visible form as well as through the quality of Sharirik Dhatu (qualitative form of bodily tissues). Aacharya describes this quality of bodily tissues (Dhatu) as a Dhatu Sarata, a concept that is given in classical texts. With the help of this concept, assessment of strength (Bala) and stability (samhanan) of the human body can be done. In Rachana Sharir, Dhatu Sarata gives proper information on compactness, resilience, and resistance of body tissues, which are responsible for the physical strength of an individual. This present study examines Dhatu Sarata through Rachana Sharir (anatomical) perspective through critical analysis of descriptions found in classical texts (Charak Samhita, Sushruta Samhita, Ashtang Hridayam), along with relevant observations reported in contemporary Ayurvedic research. This study highlights Dhatu Sarata as an indicator of structural strength and stability of the human body and explains that the variation in the strength and stability of the individual depends on the Dhatu Sarata.